2004
DOI: 10.1097/00006231-200405000-00016
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of bone scintigraphy in the diagnosis of infected joint prostheses?

Abstract: When infection of a prosthesis is suspected the diagnostic procedure should start with a WBC scan followed, if positive, by a BM scan. This procedure reduces the cost, the time required for a diagnosis, and the dose of radiation received by the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 6 publications
1
24
0
3
Order By: Relevance
“…99m Tc-MDP bone scintigraphy has been the most extensively examined radionuclide study for a painful joint replacement (14). Although increased periprosthetic uptake on a bone scan is suggestive of infection, other conditions including trauma, fractures, tumors, heterotopic ossification, and inflammatory disorders can result in an increased uptake in the periprosthetic tissue and may cause false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc-MDP bone scintigraphy has been the most extensively examined radionuclide study for a painful joint replacement (14). Although increased periprosthetic uptake on a bone scan is suggestive of infection, other conditions including trauma, fractures, tumors, heterotopic ossification, and inflammatory disorders can result in an increased uptake in the periprosthetic tissue and may cause false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Reinartz found a mean sensitivity/specificity of 78 % /84 % for diagnosing THR loosening with triple-phase bone scans (Reinartz 2009). It was also concluded, that bone scans of THR's are highly sensitive but not specific (Segura et al, 2004). The lowest sensitivity was found by Zilkens et al with a value of 50 % (Zilkens et al, 1988), while the lowest specificity was 38 % (Ovesen et al, 2003).…”
Section: Scintigraphymentioning
confidence: 96%
“…6). Usually, a two-phase or triple-phase bone scan is generated (Segura et al, 2004). The triple-phase bone scan is an enhancement with a reputation of high sensitivity (Reinartz 2009) and uses gallium scans to improve its specificity (Kraemer et al, 1993).…”
Section: Scintigraphymentioning
confidence: 99%
“…Tc-nanocolloids scintigraphy has also shown high diagnostic accuracy, but with limited clinical application due to advantages of competing modalities (ultrasound, MRI, and bone scintigraphy), mainly their broad availability. PET with 18 F-FDG or 11 C-choline has been studied for imaging of synovial infl ammation and measurement of cell proliferation and has been proved to have high diagnostic accuracy [ 17 ]. Although scintigraphy with either 99m Tc-nanocolloids or bisphosphonates could be employed in the diagnosis of RA at its early stages, its role in the evaluation of response to treatment requires repeated imaging as often as every 6-12 weeks.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…However, recent studies have shown that 67 Ga offers no advantages over 18 F-FDG PET/CT for imaging of infl ammatory diseases; therefore, Ga scintigraphy has been largely replaced by PET/CT for such a purpose [ 26 ].…”
Section: Sarcoidosismentioning
confidence: 99%